A Low Power‐consumption and Transient Nonvolatile Memory Based on Highly Dense All‐Inorganic Perovskite Films (Adv. Electron. Mater. 9/2022). (7th September 2022) - Abbas, Ghulam; Hassan, Muhammad; Khan, Qasim; Wang, Haifei; Zhou, Guigang; Zubair, Muhammad; Xu, Xiuru; Peng, Zhengchun
Abstract : Intelligent Electronics Highly crystalline CsPbBr3 films with dense and well‐connected grains, as well as uniform thickness, are fabricated by a solution‐processable two‐step spin‐coating method. Memory devices based on such films exhibit low power consumption, long‐term data retention and transient behavior, which are desirable for next generation data storage devices and neuromorphic computing. More details can be found in article number 2101412 by Xiuru Xu, Zhengchun Peng, and co‐workers.